2011
DOI: 10.1088/2041-8205/739/2/l36
|View full text |Cite
|
Sign up to set email alerts
|

Co Ice Photodesorption: A Wavelength-Dependent Study

Abstract: UV-induced photodesorption of ice is a non-thermal evaporation process that can explain the presence of cold molecular gas in a range of interstellar regions. Information on the average UV photodesorption yield of astrophysically important ices exists for broadband UV lamp experiments. UV fields around low-mass pre-main sequence stars, around shocks and in many other astrophysical environments are however often dominated by discrete atomic and molecular emission lines. It is therefore crucial to consider the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
240
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(265 citation statements)
references
References 22 publications
22
240
3
Order By: Relevance
“…As expected from the work by Fayolle et al (2011), an ice irradiated with light from the MDHL running on the H 2 :He mixture (suppressed 160 nm emission) photodepletes less rapidly than the ice irradiated with pure H 2 that exhibits a molecular emission that is roughly two times bigger. Obviously, this photodepletion value is different for the different lamp settings, fully in agreement with the main findings of the work presented in this paper.…”
Section: Co Photodepletion Measurementssupporting
confidence: 64%
See 3 more Smart Citations
“…As expected from the work by Fayolle et al (2011), an ice irradiated with light from the MDHL running on the H 2 :He mixture (suppressed 160 nm emission) photodepletes less rapidly than the ice irradiated with pure H 2 that exhibits a molecular emission that is roughly two times bigger. Obviously, this photodepletion value is different for the different lamp settings, fully in agreement with the main findings of the work presented in this paper.…”
Section: Co Photodepletion Measurementssupporting
confidence: 64%
“…(Cruz-Diaz et al 2014a,b) Recently, Chen et al (2014) showed that the differences in CO photodesorption rates reported by various groups over the past decade may be partly explained by differences in MDHL emission spectra. Carbon monoxide is an excellent example, since it strongly absorbs 160 nm photons while Lyman-α photons are clearly off resonance, as has been shown in independent experiments (Fayolle et al 2011;Cruz-Diaz et al 2014a).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Temperature programmed desorption experiments now routinely probe thermal desorption of both pure and mixed ices, providing binding energies that can be used in models [43][44][45] 54 . The process of photodesorption has been measured quantitatively and found to be much more efficient than previously thought 55,56 , and to depend strongly on the wavelength of the incident radiation field 57,58 . Details of the formation of complex organic molecules by UV irradipc, 1 arcsec corresponds to n×100 AU diameter, or n× 100× the Sun-Earth distance.…”
Section: Laboratory Experimentsmentioning
confidence: 89%